Effects of light exercise added to contrast-water immersion on recovery after an exhaustive intermittent exercise. - Deley, G.; Denuziller, J.; Babault, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: For athletes, the development of strategies that would optimize recovery and speed performance restoration is essential. Among them, contrast water immersion (CWI) is one of the most popular (Hing et al. 2008). Due to temperature changes, this technique is supposed to increase blood flow and enhance the removal of metabolic by-products, consequently speeding recovery (Vaile et al. 2008, Hing et al. 2008). However, it has been suggested that vaso-pumping induced by CWI might be insufficient to induce significant effects on blood flow (Wilcock et al. 2006). We hypothesized that adding light pedalling during water immersion might maximize the effects of recovery. The aim of the present experiment was therefore to investigate the efficacy of CWI associated with light pedalling to recover from an exercise inducing a great metabolic fatigue. Methods: Thirty-three young healthy male subjects physically active participated in this study. They were randomly assigned to one of the three experimental groups: (i) passive contrast water immersion (CONTRAST), (ii) contrast water immersion with light pedaling (ACTIVE), and (iii) passive rest at room temperature (PASSIVE). Recovery was applied during 30 minutes after a fatiguing exercise composed of four Wingate Anaerobic Test (WAnT) separated by 30 seconds of passive rest. Counter-movement jump, blood lactate concentration as well as peak power and mean power developed during a WAnT were recorded before and immediately after the fatiguing exercise. Measurements were repeated after the 30-minute recovery intervention and after an additional 30-minute period of passive rest. Results: After 30 minutes of the CONTRAST intervention, jump height was back to Pre values, whereas values were still depressed after 60 minutes in the other groups (P<0.05). Conversely, lactates were back to their initial values after 30 minutes of ACTIVE recovery (P<0.05), whereas 60 minutes and more were necessary for the PASSIVE and CONTRAST conditions. Performances to WanT were back to their initial values after 30 minutes of recovery, whatever the intervention. Discussion: The present results are in favor of the utilization of CWI after an exhaustive exercise (as compared with passive). Surprisingly, we found that despite a greater clearance of blood lactate when light pedalling was added during CWI, jump performances returned faster to normal after passive immersion. These results suggest that the intervention to be chosen depends on the aim of recovery (lactates elimination or subsequent performance).